2001
DOI: 10.1039/b102488b
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion and calibration properties of microdialysis sampling membranes in biological media

Abstract: The diffusion and calibration properties for three commercially available microdialysis membranes (polycarbonate-polyether (PC), polyacrylonitrile (PAN), and cuprophan (CUP)) were evaluated. The analytes studied had molecular weights between 94 (phenol) and 1355 (vitamin B12). For each analyte-membrane pair, an effective membrane diffusion coefficient was calculated. Effective membrane diffusion coefficients varied considerably between the microdialysis membranes. For Vitamin B12, CUP and PAN membranes gave re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 37 publications
1
19
0
1
Order By: Relevance
“…Furthermore, the EE of the solute is significantly compromised and reduced as the molecular weight of the analyte begins to approach approximately 25% or greater of the MD membrane MWCO (Snyder et al 2001;Schutter et al 2004;Cynthia and Stenken 2014). Therefore, 3,000 kDa MWCO plasmapheresis type membranes are often used (Winter et al 2002;Clough et al 2007).…”
Section: Total Protein Extraction Efficiencymentioning
confidence: 99%
“…Furthermore, the EE of the solute is significantly compromised and reduced as the molecular weight of the analyte begins to approach approximately 25% or greater of the MD membrane MWCO (Snyder et al 2001;Schutter et al 2004;Cynthia and Stenken 2014). Therefore, 3,000 kDa MWCO plasmapheresis type membranes are often used (Winter et al 2002;Clough et al 2007).…”
Section: Total Protein Extraction Efficiencymentioning
confidence: 99%
“…The membrane MWCO is defined using kidney dialysis parameters rather than what the membrane can achieve as a MWCO with it incorporated into a microdialysis sampling device. The actual recovered molecular weights through dialysis membranes have been described and show that extraction efficiency is significantly compromised and reduced as the solute molecular weight begins to approach approximately 25% or greater of the membrane MWCO (Schutte et al, 2004; Snyder et al, 2001). This causes significant challenges with cytokines since many can be in the range of the MWCO.…”
Section: 0 Microdialysis Sampling In Studying Fbr and Macrophage Pomentioning
confidence: 99%
“…The recoveries and apparent membrane diffusion coeffi cients for 10 different compounds spanning a molecular -weight range between 94 and 1355 Da and possessing different log P values were reported in a separate study [33] . For several compounds it was found that recovery was affected dramatically by the type of membrane used.…”
Section: Sampling Parameter Considerationsmentioning
confidence: 99%